Global Aging and Declining World Interest Rates : Macroeconomic Insurance Through Pension Reform in Cyprus - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2008)
How will the world-wide decline in real interest rates associated with global aging affect small open economies (SOEs) with aging populations? Lower interest rates will result in higher capital-labor ratios and increased wages; higher wages, in turn, will be passed on to pension benefits, exacerbating aging-related fiscal pressures. The pass-through effect will be stronger if pensions are indexed to nominal wages rather than prices. Using an overlapping generations model, the paper illustrates the interest rates transmission mechanism and its interaction with pension indexation for the case of Cyprus. In addition, the paper evaluates the capacity of pension reforms to insure the economy against long-run movements in world interest rates. It concludes that pension reforms, particularly those that change the indexation of pensions from wages to prices, provide substantial macro-insurance and shock absorption benefits.